2007
DOI: 10.1007/s11239-006-9028-1
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume in patients with isolated coronary artery ectasia

Abstract: Coronary artery ectasia (CAE) is frequently considered to be an incidental angiographic finding; however, several reports have shown an association with myocardial ischemia and infarction. In this study, we aimed to evaluate the mean platelet volume (MPV), which is a marker of platelet reactivity, in patients with isolated CAE. In this study we investigated the platelet functions by MPV measurement in patients with isolated CAE. The study population consisted of 23 patients (17 males, 6 females) with isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
2
10
1
2
Order By: Relevance
“…We have also showed that the patients with CAE had a lower platelet count than in patients with controls in contrast to previous studies [16,17]. In these previous studies, the authors have found no significant difference in platelet count between CAE and control groups.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…We have also showed that the patients with CAE had a lower platelet count than in patients with controls in contrast to previous studies [16,17]. In these previous studies, the authors have found no significant difference in platelet count between CAE and control groups.…”
Section: Discussioncontrasting
confidence: 76%
“…Recently published two studies [16,17] showed that MPV, another simple marker of platelet activation, was found to be elevated in patients with CAE compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22] Futhermore, Han et al [23] reported that MPV is a predictive marker for stroke or CAD, and Greisenegger et al [24] determined that an elevated MPV is associated with a poorer outcome for acute ischemic cerebrovascular events independent of other clinical parameters. Previous studies have also reported that high MPV levels are related with cardiovascular risk [25] and that these levels increase in patients with cardiac conditions [26][27][28] who have a poor prognosis.…”
Section: Discussionmentioning
confidence: 95%
“…Artan ekstrasellüler matriks yıkımı negatif remodeling ile sonuçlanır. PON aynı zamanda serbest radikallerin temizlenmesinde rol oynar ve bu radikallerin hücrenin yapısal komponentleri olan lipitler ve DNA üzerinde bulunan yapısal proteinlere vereceği zararı da azaltabilir (28)(29)(30)(31)(32)(33)(34). Pek çok yönden benzer bir patoloji olan aterosklerozun patogenezinde artan serbest radikallerin LDLK oksidasyonu yanın-da diğer hücresel komponentlere vermiş oldukları zarar da önem-lidir (28,35).…”
Section: Discussionunclassified